Okuläre Zeichen eines mitochondrialen trifunktionalen Proteindefekts: eine Langzeitbeobachtung - Ach, Thomas; Kolling, Gerold; Rohrschneider, Klaus; Haas, Dorothea; Schmidt-Bacher, Annette (Der Ophthalmologe, 2012)
A 13-year-old boy presented with a defect of the mitochondrial trifunctional protein (MTP). The MTP complex catalyses ß-oxidation of long chain fatty acids. Disorders of this multienzyme complex result in accumulation of hydroxylated long chain fatty acids which leads to chorioretinopathy. Ophthalmoscopic findings in these patients include fine hyperpigmentation while autofluorescence reveals hyperfluorescent granules at the posterior pole. Visual acuity, visual fields and electroretinography are within the normal range. A special long chain fatty acid-reduced diet seems to delay the progression of chorioretinopathy.
Gesehen am 12.11.2018